Math, asked by khushuragni, 6 months ago

Prove:
\frac{cos\theta cot\theta } {1+sin\theta} = csc\theta - 1

Answers

Answered by EthicalElite
13

To Prove :

 \sf \dfrac{cos\theta cot\theta } {1+sin\theta} = cosec\theta - 1

⠀ ⠀⠀ ⠀ ⠀⠀ ⠀

Proof :

⠀ ⠀ ⠀⠀ ⠀

LHS :

 \sf \dfrac{cos\theta cot\theta } {1+sin\theta}

⠀ ⠀ ⠀⠀ ⠀

We know that :

 \large \underline{\boxed{\bf{cot \theta = \dfrac{cos\theta }{sin \theta}}}}

 \sf : \implies \dfrac{cos\theta \times \dfrac{cos\theta}{sin\theta}} {1+sin\theta}

 \sf : \implies \dfrac{\dfrac{cos^{2} \theta}{sin\theta}} {1+sin\theta}

 \sf : \implies \dfrac{cos^{2} \theta}{sin\theta} \times \dfrac{1}{1+sin\theta}

⠀ ⠀ ⠀⠀ ⠀

By rationalisation :

 \sf : \implies \dfrac{cos^{2} \theta}{sin\theta} \times \dfrac{1}{1+sin\theta} \times \dfrac{1-sin\theta}{1-sin\theta}

 \sf : \implies \dfrac{cos^{2} \theta}{sin\theta} \times \dfrac{1(1-sin\theta)}{(1+sin\theta)(1-sin\theta)}

 \sf : \implies \dfrac{cos^{2} \theta}{sin\theta} \times \dfrac{1-sin\theta}{(1)^{2}-(sin\theta)^{2}}

 \sf : \implies \dfrac{cos^{2} \theta}{sin\theta} \times \dfrac{1-sin\theta}{1 - sin^{2} \theta}

⠀ ⠀ ⠀⠀ ⠀

Now, We know that :

 \large \underline{\boxed{\bf{1 - sin^{2} \theta = cos^{2} \theta}}}

 \sf : \implies \dfrac{cos^{2} \theta}{sin\theta} \times \dfrac{1-sin\theta}{cos^{2} \theta }

 \sf : \implies \dfrac{\cancel{cos^{2} \theta}}{sin\theta} \times \dfrac{1-sin\theta}{\cancel{cos^{2} \theta} }

 \sf : \implies \dfrac{1-sin\theta}{sin\theta}

 \sf : \implies \dfrac{1}{sin\theta}  - \dfrac{sin \theta}{sin\theta}

 \sf : \implies \dfrac{1}{sin\theta}  - \cancel{\dfrac{sin \theta}{sin\theta}}

 \sf : \implies \dfrac{1}{sin\theta}  - 1

⠀ ⠀ ⠀⠀ ⠀

Now, We know that :

 \large \underline{\boxed{\bf{\dfrac{1}{sin\theta} = cosec \theta}}}

 \sf : \implies cosec \theta  - 1

⠀ ⠀ ⠀⠀ ⠀

RHS :

 \sf cosec\theta - 1

⠀ ⠀ ⠀⠀ ⠀

As, LHS = RHS,

Hence, proved.

Answered by mayank16937
6

Answer:

bro if any problem please tell me

Similar questions